DESIGNING THE EDUCATIONAL SPACE OF A PRESCHOOL EDUCATION INSTITUTION AS A CONDITION FOR CHILD DEVELOPMENT - Попиченко, С.С.; Крамська, З.М. (SWorldJournal, 2024)
The article summarizes the main provisions in areas related to the development of the child's personality. The characteristics of the preschool education system of Ukraine are offered. The principles of educational space design are presented. The implemen